Sustainable development in chemical and biological engineering education - Elnashaie, Said Salah Eldin Hamed; Wan Ab. Karim Ghani, Wan Azlina; Mohd Salleh, Mohamad Amran; Awang Biak, Dayang Radiah; Ali, Salmiaton (Elsevier, 2013)
Sustainable development and integrated bio-refineries are modern concepts in the chemical and biological engineering discipline for the economic development and sustainability of all countries. An integrated system approach based on system theory is used to investigate the systems and subsystems and their relation to education. Introduction of sustainable development into chemical and biological engineering education is suggested using two general approaches. Decentralized approach introducing them in a well-chosen good number of courses and centralized approach introducing specific courses on sustainable development and its subsystems as compulsory courses. This paper will discuss both approaches with special emphasis to possible application to a Malaysian and USA departments.